Persepsi Siswa Sekolah Menengah Atas (SMA) terhadap Perpustakaan Proklamator Bung Hatta Bukittinggi - Putra, Agung Dwino; Nelisa, Malta (Ilmu Informasi Perpustakaan dan Kearsipan, 2019)
AbstractÂ The purpose of this research are (1) find out how the perceptions of high school students towards the librarians of the Bung Hatta Proclamator Library. (2) find out how the perceptions of senior high school students to the collection of Bung Hatta Proclamator Library. (3) knowing how perceptions of senior high school students to the services of Bung Hatta's Proclamator Library. (4) knowing the perceptions of high school students on Bung Hatta Proklamator Library facilities.Keywords: Perceptions, Students, Bung Hatta's Proclamator Library